Cyberbullying Ditinjau Dari Traits Kepribadian Conscientiousness Pada Siswa Kelas XI SMA Swasta Bodhicita Medan - Velda Limanto; Achmad Irvan Dwi Putra; Sarinah Sarinah (Mahesa Research Center, 2019)
This study aims to determine the relationship between conscientiousness personality traits and cyberbullying. The hypothesis proposed in this study is that there is a negative relationship between the traits of conscientiousness personality and cyberbullying. The research subjects used in this study were class XI students of Bodhicita Private High SchoolMedan, totaling 119 people. Data is obtained from a scale to measure the traits of conscientiousness and cyberbullying personality. Calculations are carried out by conducting an analysis prerequisite test (assumption test) consisting of a normality test and a linearity test. Analysis of the data used is using Product Moment correlation through SPSS 20 for Windows. The results of data analysis showed a correlation coefficient of -0.575 and a significance value of 0.000 (p <0.05). The results of this study indicate that the contribution given to the conscientiousness personality traits variable towards cyberbullying is 33.1 percent, the remaining 66.9 percent is influenced by other factors not examined. From the results of this study it can be concluded that the research hypothesis there is a negative relationship between the traits of conscientiousness personality and acceptable cyberbullying.